Suboptimal Clinical Documentation in Young Children with Severe Obesity at Tertiary Care Centers. (6th September 2016) - Brady, Cassandra C.; Thaker, Vidhu V.; Lingren, Todd; Woo, Jessica G.; Kennebeck, Stephanie S.; Namjou-Khales, Bahram; Roach, Ashton; Bickel, Jonathan P.; Patibandla, Nandan; Savova, Guergana K.; Solti, Imre; Holm, Ingrid A.; et al.
Abstract : Background and Objectives. The prevalence of severe obesity in children has doubled in the past decade. The objective of this study is to identify the clinical documentation of obesity in young children with a BMI ≥ 99th percentile at two large tertiary care pediatric hospitals. Methods. We used a standardized algorithm utilizing data from electronic health records to identify children with severe early onset obesity (BMI ≥ 99th percentile at age <6 years). We extracted descriptive terms and ICD-9 codes to evaluate documentation of obesity at Boston Children's Hospital and Cincinnati Children's Hospital and Medical Center between 2007 and 2014. Results. A total of 9887 visit records of 2588 children with severe early onset obesity were identified. Based on predefined criteria for documentation of obesity, 21.5% of children (13.5% of visits) had positive documentation, which varied by institution. Documentation in children first seen under 2 years of age was lower than in older children (15% versus 26%). Documentation was significantly higher in girls (29% versus 17%, p < 0.001 ), African American children (27% versus 19% in whites, p < 0.001 ), and the obesity focused specialty clinics (70% versus 15% in primary care and 9% in other subspecialty clinics, p < 0.001 ). Conclusions. There is significant opportunity for improvement in documentation of obesity in young children, even years after the 2007 AAP guidelines for management of obesity.